رقمنة مصالح أنظمة الضرائب والجمارك في الجزائر ودورها في الأداء الاقتصادي - غربي، طارق; خضير، عقبة; مصطفاوي، علي (University Of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى تسليط الضوء على رقمنة النظام الضريبي والجمركي ودورها في تحسين الأداء الاقتصادي الجزائري. تناولنا مفهوم الرقمنة وواقع استخدامها في كل من النظامين الجبائي والجمركي بالجزائر، بالإضافة إلى دور الرقمنة في الحد من ظاهرتي التهرب والغش في الاقتصاد الوطني، لقد استخدمنا المنهج الوصفي التحليلي للوصول إلى النتائج التالية: وجدنا أن الجزائر بدأت تتوجه نحو رقمنة النظام الضريبي بإطلاق نظام المعلومات الجبائي "جبايتك"، وهو نظام إلكتروني حديث يركز على عمليات التصريح والتحصيل الضريبي. أما فيما يخص قطاع الجمارك، بدأت الرقمنة باستخدام نظام (SIGAD) لتسريع العملية وتطبيق معايير الشفافية وتعزيز الرقابة ودقة الإحصاءات التجارية الخارجية، ثم انتقلت إلى النظام الجديد (E – DOUANE) الذي يهدف إلى تحسين إدارة العمليات وتحديثها بما يتماشى مع التطورات التكنولوجية الحديثة. Abstract: This study aims to shed light on the digitization of the tax and customs system and its role in improving Algerian economic performance. We dealt with the concept of digitization and the reality of its use in both the tax and customs systems in Algeria, in addition to the role of digitization in reducing the phenomena of evasion and fraud in the national economy, we used the descriptive and analytical approach to reach the following results: We found that Algeria is moving towards digitizing the tax system with the launch of the tax information system "Leviatech", a modern electronic system focused on tax declaration and collection processes. As for the customs sector, digitization began using the SIGAD system to speed up the process, apply transparency standards, enhance control and accuracy of foreign trade statistics, and then moved to the new system (E-DOUANE), which aims to improve and modernize the management of operations in line with modern technological developments.
Digitization of the services of tax and customs systems in Algeria and their role in economic performance
مداخلة
Keywords: الرقمنة; قطاع الضرائب; قطاع الجمارك; Digitalization; Tax sector; Customs sector